Kairós e o tempo ritual sagrado em Edmund Leach: uma investigação à luz dos significados do mito de Kairós - Souza, Tamara Pereira de (2015)
In recent years, more specifically since the modern era, the phenomena rituals have been object of formation of concepts both in the context of the studies of Sciences of Religion, as well as of the social sciences. Within this perspective, Edmund Leach proposed a model of time ritual where in each intermission of ritual festivities, situated between periods of social life, represents a change from the normal order-profane existence to the unusual order-sacred and thus retroactively. However, when addressing the knowledge about the intermission of Sacred Time, in Leach configured in his own time ritual proposal and conceived as a taboo area, marginal, from another world, we have identified that this represents an area insufficiently studied by the same author who interpreted this ritual domain exclusively, from mythological elements associated with the notion of Cronus, leading us to assume that some issues have been "hidden". .In this respect, and taking as a reference that, for some traditions of ancient Greece, the time was designed from a dual perspective, our research focused on an interpretation of Sacred time interval, in Leach in the light of Kairos. This research which was developed based on the bibliographical research method, reached results indicating that while the time interval, in Leach interpreted in the light of the myth of Cronus, manifests itself as part of a linear sequence which combines switchovers and stops between Sacred Time while this same interval ritual associated with kairological time, denotes not a part of time, but its origin or an outburst of eternity in time pulsing between speed (continuum) and immobility, follows an irreversible and one-way course when time rewinds and stops. It is expected from the results of this research to contribute to the context of the Sciences of Religion, Social Sciences and Psychology regarding the knowledge of the Sacred Time in Leach as benchmarks for future researchers who intend to discuss and deepen the theme